(untitled) (Research, Society and Development, 2021)
Thymol and carvacrol are the main compounds found in Lippia mycrophylla essential oil (LM-OE) and have presented some spasmolytic effects. This work was designed to explore a possible vasorelaxant effect of LM-OE and its major monoterpenes constituents on rat pulmonary artery. For that, the organ was in vitro stimulated with phenylephrine (Phe) 3 mM and over the tonic contraction the relaxant effect of LM-OE, carvacrol and thymol was observed in both intact and denuded-endothelium. Moreover, atropine, L-NAME, indomethacin, 2,3-O-isopropylidene adenosine, H-89 and Y-27632 were incubated before the relaxant curve of thymol over Phe-tonic contraction. Furthermore, the effects of thymol on KCl 30 or 80 mM and S-(−)-Bay K8644-induced tonic contractions were evaluated, as well as its inhibitory effect on CaCl2-induced cumulative contractions. LM-OE, carvacrol and thymol presented relaxant effect on pulmonary artery, thymol was the most potent and its relaxant potency in intact-endothelium preparations was reduced by atropine, L-NAME, indomethacin, 2,3-O-isopropylidene adenosine and H-89, despite there was not change on its maximum relaxat effect. Also, the monoterpene relaxed equipotently KCl 30 or 80 mM pre-contracted pulmonary artery, antagonized CaCl2-induced cumulative contractions and relaxed S-(−)-Bay K8644 pre-contracted organ. Ultimately, thymol relaxant potency was not modified by Y-27632. Therefore, thymol acts by endothelium-dependent and independent mechanisms, possibly positively modulating the endothelial cholinergic pathway, prostanoids release and further activation of AC/PKA and also inhibiting Ca2+ influx through CaV.